Mass murder in the United States: a history - Duwe, Grant (McFarland, 2007)
The patterns and prevalance of mass murder -- The first mass murder wave, 1900-1939 -- The trough between the waves, 1940-1965 -- The second mass murder wave, 1966-1999 -- The news media's presentation of mass murder -- The social construction of mass murder